Dragon ball super, Broly [videorecording (DVD)] : the movie - Nagamine, Tatsuya; Sabat, Christopher R; Sabat, Christopher R (FUNimation, 2019)
Goku and Vegeta unexpectedly encounter Saiyan warrior Broly on Earth after he was exiled to the distant planet Vampa.